2018
DOI: 10.3390/nu10060762
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Diet Supplementation with Lactobacillus paracasei K71 Prevents Age-Related Cognitive Decline in Senescence-Accelerated Mouse Prone 8

Abstract: This study aimed to assess the suppressive effect of long-term diet supplementation with Lactobacillus strains on cognitive decline in the senescence-accelerated mouse prone 8 (SAMP8) model. For 43 weeks, fourteen-week-old female SAMP8 mice were fed a standard diet containing 0.05% (w/w) Lactobacillus casei subsp. casei 327 (L. 327) or Lactobacillus paracasei K71 (L. K71) derived from rice grains and sake lees, respectively. SAMP8 mice that were fed a L. K71-supplemented diet had better cognitive performance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 33 publications
3
39
0
Order By: Relevance
“…Similarly, Kadry & Megeed (2018) found that Lactobacillus could effectively inhibit the reduction of BDNF induced by cadmium chloride in the hippocampus of mice. Moreover, Corpuz et al (2018) reported that Lactobacillus paracasei K71 prevents age-related cognitive decline in senescence-accelerated mouse prone 8 by increasing the protein expression of BDNF and the phosphorylation of CREB in the hippocampus. Neuroplasticity also needs the regulation of NCAM (Seidenfaden, Krauter & Hildebrandt, 2006) and the stimulation of SCF (Jin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kadry & Megeed (2018) found that Lactobacillus could effectively inhibit the reduction of BDNF induced by cadmium chloride in the hippocampus of mice. Moreover, Corpuz et al (2018) reported that Lactobacillus paracasei K71 prevents age-related cognitive decline in senescence-accelerated mouse prone 8 by increasing the protein expression of BDNF and the phosphorylation of CREB in the hippocampus. Neuroplasticity also needs the regulation of NCAM (Seidenfaden, Krauter & Hildebrandt, 2006) and the stimulation of SCF (Jin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, probiotic colonization may be optional for their effects to manifest. For instance, heat-killed L. paracasei benefited the human and animal host, in terms of neurochemical and behavioral changes (Corpuz et al, 2018;Murata et al, 2018;Wei et al, 2019). Some probiotics, such as L. reuteri, L. paracasei, L. plantarum, L. gasseri, L. kefiranofaciens, B. breve, and B. infantis, promoted the colonization of other beneficial microbes that contributed to the reduction of depressive-like symptoms in animals (Marin et al, 2017;Dhaliwal et al, 2018;Jang et al, 2019;Sun et al, 2019;Tian et al, 2019;Wei et al, 2019).…”
Section: Heterogeneity Of Gut Microbiota Compositionmentioning
confidence: 99%
“…Behavioral assessments for memory function in mice include the Morris water maze, Barnes maze and other behavioral tests (Dedic et al, 2011). Administration of probiotics including L. helveticus (Ohland et al, 2013;Luo et al, 2014;Liang et al, 2015), L. plantarum (Dhaliwal et al, 2018), and L. paracasei (Corpuz et al, 2018;Huang et al, 2018) enabled animals to perform these memory test more effectively. Attention, memory and learning behaviors in humans are assessed by cognitive tests, such as the Stroop, verbal-learning and digit-symbol tests.…”
Section: Heterogeneity Of Depressionmentioning
confidence: 99%
“…The spatial learning and memory ability of mice was evaluated using the Barnes maze test as previously described [19]. The escape latency to reach the escape box and staying time in each quadrant were recorded during the probe test.…”
Section: Barnes Maze Testmentioning
confidence: 99%